2018
DOI: 10.1111/joop.12217
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing in interteam responses to disaster

Abstract: Research demonstrates that information sharing is facilitated by familiarity, and having a common understanding of problems, use of lexicon, and semantic meaning. These factors can be difficult to develop within extreme environments such as disasters as members of the multi‐agency system that responds often have limited experience of working together. Public inquiries repeatedly highlight the impact of information sharing difficulties on public safety, but limited academic research has focused on identifying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 69 publications
(104 reference statements)
1
81
2
Order By: Relevance
“…Naturalistic Decision Making (NDM) research examines how decisions are made in dynamic, real-world contexts characterized by time pressure, risk, uncertainty, shifting and competing goals, and accountability pressure (Lipshitz et al 2001). This often includes extreme environments in which lives are at stake, such as military combat (Thunholm 2005), firefighting (Klein et al 1986), counter-terrorism policing (van den Heuvel et al 2012), and disaster response (Waring et al 2018). Findings from this domain highlight the importance of access to relevant information for developing an accurate understanding of the situation and how it may progress to tailor decisions and actions (Rankin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Naturalistic Decision Making (NDM) research examines how decisions are made in dynamic, real-world contexts characterized by time pressure, risk, uncertainty, shifting and competing goals, and accountability pressure (Lipshitz et al 2001). This often includes extreme environments in which lives are at stake, such as military combat (Thunholm 2005), firefighting (Klein et al 1986), counter-terrorism policing (van den Heuvel et al 2012), and disaster response (Waring et al 2018). Findings from this domain highlight the importance of access to relevant information for developing an accurate understanding of the situation and how it may progress to tailor decisions and actions (Rankin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Building on the above-mentioned works and further readings (Endsley 1995;Balcik and Beamon 2008; Groenendaal et al 2013;Radisch et al 2013;Waring et al 2018), five functions were selected as tasks that structured the interview design-situation assessment; decision making; coordination, command, and control; logistics; and communication with the public (Table 2).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…How it is used is partially determined by organizational structures and the management of information within and across organizations. Many organizations are organized in a three-tiered hierarchical command structure, with decisions being fed from strategic (responsible for setting overall objectives) to tactical (setting parameters and level of autonomy for operational level to work to) and operational (managing the incident ground) level (Waring et al 2018).…”
Section: Coordination Command and Controlmentioning
confidence: 99%
“…In the disaster recovery area, Waring et al studied mechanisms that influence information exchange between emergency response teams. Their analyses revealed that clearly stated rationale, proper assignment of roles, and well‐established procedures facilitate the IS, while limited SA and incapacitated expression of information impede it.…”
Section: Related Workmentioning
confidence: 99%